Pelayanan dan Tata Kelola Sampah di Kawasan Perkotaan: Studi Kasus Kecamatan Medan Baru - Abdilla, Irfan; Irmayani, Tengku; Ridho, Hatta (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
The problem of waste management in urban areas is a complex challenge and requires a responsive and participatory approach to governance. This study aims to evaluate the quality of waste management services and the effectiveness of the policy of delegating authority to the sub-district head in Medan Baru District, Medan City. Using a qualitative descriptive approach, data was collected through in-depth interviews, field observations, and documentation. The results of the study show that waste management services still face various obstacles, especially in the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Limited facilities and infrastructure, irregular transportation schedules, low response to complaints, lack of officer training, and lack of an empathetic approach are the main obstacles. On the other hand, the delegation of authority has not been fully supported by institutional capacity, inter-agency coordination, and adequate community participation. This research emphasizes the importance of institutional strengthening, increasing operational capacity, and active community involvement in realizing effective and sustainable waste management at the sub-district level.